Bohemian. (Amsterdam : C-I International, 1992)
For Fall '92 six international artists were again chosen to present their art on Bohemian shirts and complete the seventh art inspired shirt collection.
boek
Keywords: Kunc, Milan; Adamski, Hans-Peter, -- 1947-; Shkof, Daryush; Anderson, Curtis; Trockel, Rosemarie; Schulze, Andreas